Drancourtella massiliensis gen. nov., sp. nov. isolated from fresh healthy human faecal sample from South France - Durand, G.A. (New Microbes New Infect, 2016)
Strain GD1(T) gen. nov., sp. nov., is the type strain of the newly proposed genus and species Drancourtella massiliensis, belonging to the Clostridiales order. This strain, isolated from the stool of a healthy person, is a Gram-positive rod, oxygen intolerant and nonmotile, with spore-forming activity. The features of this organism and its genome sequence are described. The draft genome is 3 057 334 bp long with 45.24% G + C content; it contains 2861 protein-coding genes and 64 RNA genes.